Dietary and herbal supplement consumer health information for pain: A cross-sectional survey and quality assessment of online content - Jeremy Y Ng; Sahar Popal; Sathurthika Selvanayagam (Integrative Medicine Research)
Background: Patients are increasingly utilizing the internet to learn about dietary and herbal supplements (DHSs) for various diseases/conditions, including pain management. Online health information has been found to be inconsistent and of poor quality in prior studies, which may have detrimental effects on patient health. This study assessed the quality of online DHSs consumer health information for pain. Methods: Six search items related to DHSs and pain were used to generate the first 20 websites on Google across four English-speaking countries. The identified 480 webpages produced 68 eligible websites, which were then evaluated using the DISCERN tool. The mean scores and standard deviations (SD) of the reviewers’ ratings on each of the 15 DISCERN instrument items as well as the overall total score were calculated. Results: The mean summed score for the 68 eligible websites was 46.6 (SD = 10.1), and the mean overall rating was 3.3 (SD = 0.8). Websites lacked information regarding areas of uncertainty, the effects of no treatment being used, and how treatments affect the overall quality of life. These shortcomings were especially apparent across commercial websites, which frequently displayed bias, failed to report the risks of DHS products, and lacked support for shared decision-making regarding the use of DHSs. Conclusion: Variability exists in the quality of online consumer health information regarding DHS use for pain. Healthcare providers should be aware of and provide guidance to patients regarding the identification of reliable online resources so that they can make informed decisions about DHS use for pain management.